Regulatory interactions of calmodulin-binding proteins: phosphorylation of calcineurin by autophosphorylated Ca2+/calmodulin-dependent protein kinase II. - Hashimoto, Y (1988)
The Ca2+/calmodulin (CaM)-dependent protein phosphatase calcineurin is rapidly phosphorylated (0.8 mol of 32PO4 per mol of 60-kDa subunit of calcineurin) by brain Ca2+/CaM-dependent protein kinase II (CaM-kinase II). This reaction requires the autophosphorylated, Ca2+-independent form of CaM-kinase II since Ca2+/CaM binding to calcineurin inhibits phosphorylation. However, the phosphorylation reaction does require Ca2+, presumably acting through the 19-kDa subunit of calcineurin. Calcineurin is a good substrate for CaM-kinase II, with a Km of 19 microM and Vmax of 2.4 mumol/min per mg. Phosphorylation of calcineurin changed its phosphatase activity with either a 2-fold increase in Km (32P-labeled myosin light chain as substrate) or a 50% decrease in Vmax (p-nitrophenyl phosphate as substrate). The phosphorylated calcineurin exhibited very slow autodephosphorylation (0.09 nmol/min per mg) but was effectively dephosphorylated by brain protein phosphatase IIA. Dephosphorylation, like phosphorylation, was blocked by high concentrations of Ca2+/CaM and stimulated by Ca2+ alone. Thus calcineurin has a regulatory phosphorylation site that is phosphorylated by the Ca2+-independent form of CaM-kinase II and blocked by high concentrations of Ca2+/CaM.